Legal Aspect of Relationship between Political Parties, People, and People's Representatives - Cahyawat, Dwi Putri; Hoesein, Zainal Arifin (International Journal of Criminology and Sociology, 2021)
This article discussed the topic of political party membership in the Indonesian Parliament institutions, which is based on the pattern of relations between the People's Representatives and the people they represent, and their impact in the process of forming and implementing strategic policies that rely on popular sovereignty. The article focused on the study of politics of law in the institutionalization of political parties within the parliament's institutions and the impact on the exercise of popular sovereignty. This paper has several different approaches if related to the basic theory of democracy about political links which generally examines the relationship between political parties and their voters, between politicians and citizens, and between members of parliament and their people. The results emphasize the pattern of relations between the representatives of the people and the people they represent, in connection with the institutional existence of the Indonesian parliament which is the executor of people's sovereignty.